Neuro-ophthalmologic manifestations of COVID-19: a review - Indra Tri Mahayana; Stefani Melisa Karina; Nyssa Alexandra Tedjonegoro (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Several mechanisms for the pathogenesis of COVID-19 have been proposed. These are direct viral toxicity, endothelial cell damage and thromboinflammation, dysregulated immune response, and renin-angiotensin-aldosterone system (RAAS) dysregulation. The ophthalmic manifestations of COVID-19 vary, affecting the anterior, posterior, and neuro-ophthalmic components. However, the relationship between COVID-19 and neuro-ophthalmologic presentations is limited. This literature review focuses on discussing these manifestations. A manual search was performed using the following keywords “neuro-ophthalmology”, “ocular”, “manifestations”, COVID-19, and coronavirus. The searches were conducted in PubMed and Google Scholar, where any study type and online publications were included. The most common ocular manifestation found in COVID-19 patients is conjunctival involvement. Some reported neuro-ophthalmic manifestations of COVID-19 are papillophlebitis, optic neuritis, cranial nerve palsies, Miller Fisher syndrome, Tolosa-Hunt syndrome, Adie’s tonic pupil, and internuclear ophthalmoplegia. A physician should examine the presence of diplopia, pain during eye movement, declining vision, or any other neurological symptoms. Therefore, it is essential to perform a comprehensive eye examination which includes visual acuity, pupillary response, ocular motility, ptosis, and optic disc examination. Additional tests such as neuroimaging or angiography might be performed to detect cerebral infarction or any other abnormalities when necessary. It is vital to be vigilant and consider COVID-19 as one of the possible causes of disease during this pandemic.